Integrative Entrepreneurship Education: The Case of EDEM Business School - Donaldson, Colin; Villagrasa, Jorge (Journal of Management and Business Education, 2024)
Changing economic landscapes have shifted from industrial innovation to entrepreneurial knowledge-based economies requiring educational experiences based on practice and real-world connections. Whereas much focus has centred on curricular activities to achieve this aim, in comparison there is scant attention paid to the important role that organised and spatially embedded out-of-curriculum activities can afford. We present an innovative and practical initiative that takes a systematic approach to effectively blend diverse elements from both the formal and informal curriculum, providing a holistic and immersive learning experience for aspiring entrepreneurs. By embracing a multifaceted method, the integrated model of entrepreneurship education that we detail aims to equip students with the knowledge, skills, and networks needed to navigate the complexities of entrepreneurship and excel in today's dynamic business landscape.